Reconstructing the Constitutional Theory of Mount Laurel II - John M. Payne (Washington University Journal of Law & Policy, 2000)
How close does Mount Laurel II come to declaring a constitutional right to shelter under the New Jersey Constitution?
Keywords: NAACP v. Township of Mount Laurel 456 A.2d 390 (N.J. 1983); Housing discrimination; Land use; Zoning law